Imnuty and immunosenescense - Piscoya Arbañil, José (1996)
We review the  latest insigths on the understanding of immununosenenscense, or aging of the inmune systeni. This process results from  the interaction between bothl inborn (genetic) and acquired (nutritional status, lifestyle,  and host-parasitic interaction) features. Among genetic features, genetically controled expression of HLA system molecules on inmune cells and possible linkage of some allelies expression to  longer longevity stand out. Other main features are changes of the aged patient inmune system and understand of  of thymus involution as well as changes in the distribution, quality, and quantilty of lympliocyte sub-populations. Another ¡nmunosenescence factor is the niodification ¡n the production of cytokines, regulatory liorniones of the inmune system.  Adequate understanding of above factors will lead to prevention follow-up, and inmune intervention of aged   patient strategies.